2005
DOI: 10.1111/j.1365-3164.2005.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins expression in canine intracutaneous cornifying epithelioma and squamous cell carcinoma

Abstract: Heat shock proteins (HSPs) are strongly implicated in the control of cell growth, differentiation and biological behaviour of many human cutaneous neoplasms. To our knowledge, no data have been published in the veterinary literature concerning either normal or neoplastic skin. In this study, the immunohistochemical expression of Hsp27, Hsp72 and Hsp73 was evaluated in normal canine skin, 14 intracutaneous cornifying epitheliomas (ICE), 10 well-differentiated and 5 moderately differentiated squamous cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 49 publications
7
26
0
Order By: Relevance
“…Similar studies have been conducted in veterinary medicine, but to a lesser extent. In dogs, the expression of heat shock proteins was studied in normal skin and squamous cell carcinoma of the skin (Romanucci et al 2005), as well as in canine transmissible venereal tumor (CTVT) (Beckmann et al 1990). A similar study was conducted by Rommanucci et al (2006) in mammary gland tumors in bitches.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar studies have been conducted in veterinary medicine, but to a lesser extent. In dogs, the expression of heat shock proteins was studied in normal skin and squamous cell carcinoma of the skin (Romanucci et al 2005), as well as in canine transmissible venereal tumor (CTVT) (Beckmann et al 1990). A similar study was conducted by Rommanucci et al (2006) in mammary gland tumors in bitches.…”
Section: Discussionmentioning
confidence: 96%
“…Hsp70 and Hsp90 expression were found in human breast carcinoma cells (Havik and Bramham 2007). In dogs, the expression of heat shock proteins was found in squamous cell carcinoma of the skin (Romanucci et al 2005, Bongiovanni et al 2008, cervical cancer (Chu et al 2001) and mammary gland tumors (Kumaraguruparan et al 2006, Romanucci et al 2006. Romanucci (2006) demonstrated the expression of Hsp90 in all examined tumors (simple and complex carcinomas) and found that these proteins are associated with poor outcome and are involved in carcinogenesis in the same way as heat shock protein 27.…”
Section: Introductionmentioning
confidence: 85%
“…Specific, positive-control human tissues were used for Hsp27 (normal human skin) and Hsp70 (lobular breast carcinoma and colorectal carcinoma) immunostaining according to the data sheets. Additionally, we included HSP-positive canine tissue from a squamous cell carcinoma (skin) 35 and an intestinal tubular carcinoma. Canine tissues from intestinal carcinomas with known antigen profiles (A. Benito, unpublished doctoral dissertation, 2007.)…”
Section: Methodsmentioning
confidence: 99%
“…The immunoexpression indexes were calculated as the average of percentage of positive cells in 5 representative fields for each tumor. 3,10,18,19,23,26,35,44 For each tissue section, staining was scored as absent (grade 0), mild (grade 1: <10% positive cells), moderate (grade 2: 10-50% positive cells), and high (grade 3: >50% positive cells). Grades 0 and 1 were considered to be negative.…”
Section: Methodsmentioning
confidence: 99%
“…In the cervix Hsp27 is a marker of cell differentiation, and is highly expressed during the process of squamous metaplasia (Liu et al, 2011). Romanucci et al (2005) suggested that Hsp27 should be regarded as a differentiation marker for keratinocytes, both in normal and in neoplasic canine skin.…”
Section: Discussionmentioning
confidence: 99%